تأثير النشاط البدني على بعض المتغيرات البدنية والبيوكميائية ومستوى هرمون السيرتونين لدى المعلمات المغتربات بدولة الكويت - خليل، مها خليل محمد; ذو الفقار، ريم حسن; معتوق، هاجر محمود محمد محمد Maatouq, Hajar Mahmoud Mohammed Mohammed; بدوي، سارة (جامعة حلوان - كلية التربية الرياضية للبنات, 2024)
يهدف البحث إلى تصميم برنامج النشاط البدني ومعرفة تأثيره لدى السيدات المغتربات بدولة الكويت على بعض المتغيرات البدنية متمثلة في (القوة والتحمل العضلي، السرعة، المرونة) وبعض المتغيرات البيوكميائية متمثلة في مستوى الكوليسترول الكلي، الدهون الثلاثية، الكوليسترول الضار، الكوليسترول النافع) ومستوى هرمون السيرتونين في الدم، منهج البحث: تم استخدام المنهج التجريبي لمجموعة واحدة مع قياس قبلي وبعدي نظرا لملائمته لطبيعة وفكرة البحث، عينة البحث: تم اختيار العينة بالطريقة العمدية لعدد (۱۲) معلمة من المعلمات المغتربات بمدرسة أم مالك الأنصارية الابتدائية بدولة الكويت ، خضعت المجموعة للبرنامج المقترح للتمرينات الهوائية لمدة ۱۲ أسبوع بواقع 3 وحدات تدريبة أسبوعيا زمن الوحدة ٦٠ دقيقة. وكانت من أهم النتائج: - 1- زيادة القوة العضلية التي جاءت أعلى نسب تحسن لقوة عضلات البطن في اختبار الجلوس من الرقود بنسبة %64. ۲ - تفاوت نسب التحسن لدى المجموعة التجريبية في قياس مستويات الكوليسترول الكلي في الدم حيث توجد أعلى نسب تحسن مستوى الكولسترول النافع ۳۲.۲ % . ٣- زيادة في مستوى هرمون السيرتونين (أثناء الراحة - بعد المجهود) جاءت نسبة التحسن ٤.٨ %. The research aims to design a physical activity and find out its effect among Expatriate Teachers in Kuwait on same physical variables such as (strength and muscular endurance, speed , flexibility) and some biochemical variables such as ( the level of total cholesterol , level of high density protein fats, low density protein fats and triple fats)and the level of serotonin hormone in blood. Research Methodology: the experimental method was used one group with pre-and post-measurement due to its suitability to the idea of the research. Research Sample: The sample of the research has (12) expatriate teachers and they are chosen by the intended way, they are teachers in Om Malik Al-Ansariyah Primary School in Kuwait. they use the suggested program (aerobic exercise) for (12) weeks as three units weekly, time of the unit is (60 min).the most important Results: 1- Increased muscle strength, which resulted in the highest percentage of improvement for abdominal muscle strength in the sit-up test by 64%. 2- The experimental group’s rates of improvement in measuring total cholesterol levels in the blood varied, with the highest rate of improvement in the level of beneficial cholesterol being 32.2% 3-An increase in the level of the serotonin hormone (during break- after exertion) the improvement rate was 4.8%.
Keywords: الأنشطة البدنية -- القوة العضلية -- الدهون الثلاثية -- معلمات المرحلة الابتدائية -- الكويت